Lipase catalyzed synthesis of epoxidized fatty hydrazides from epoxidizes palm oil and its application as a Clay modifier for polylactic acid/epoxidized palm oil/organoclay nanocomposites - Zakiah Jamingan (Thesis, 2020)
This study aims to improve the mechanical and degradibility of PLA (Poly (lactic acid))/EPO (epoxidized palm oil) blend by addition of epoxidized fatty hydrazine (EFH) modifiied montmorillonite (EMT). As a conclusion, EFHs can produced the organoclay which reinforcesy the mechanical properties, flexibility and degradilibility of PLA/EPO composites.